A pathway to recovery: the Critically Endangered Sumatran tiger Panthera tigris sumatrae in an 'in danger' UNESCO World Heritage Site. Issue 1 (23rd October 2017) - Pusparini, Wulan; Batubara, Timbul; Surahmat, Fahrudin; Ardiantiono; Sugiharti, Tri; Muslich, Muhammad; Amama, Fahrul; Marthy, William; Andayani, Noviar
Abstract: Reliable information on wildlife populations and the threats they face is crucial for assessing the performance of conservation strategies. As part of its efforts to improve the effectiveness of Bukit Barisan Selatan National Park in Sumatra, Indonesia, and aid the recovery of flagship species, the Park's management authority designated a 1, 000 km 2 forest block an Intensive Protection Zone. To set a baseline from which to evaluate the performance of this zone, we investigated the density of tigers Panthera tigris sumatrae, and spatio-temporal interactions between tigers, their principle prey and threats. The estimated density of tigers was 2.8 per 100 km 2, whereas in 2002 camera-trapping failed to record any tigers in the Intensive Protection Zone. We found the study area contained a rich prey base, with muntjac deer Muntiacus muntjak, macaques Macaca nemestrina and wild pigs Sus scrofa occupying 85–98% of the area, and sambar Rusa unicolor 61%. Despite these promising findings we also recorded a relatively high number of people entering the Park illegally, with 77 incidents over 6 months, of which 20% involved armed poachers. The poachers operated mainly at night and were concentrated in two locations. Law enforcement patrol teams were active during the day, and therefore had little overlap with the poachers. Prioritizing these at-risk areas for increased protection by rangers would further secure the Intensive Protection Zone, and expanding ranger activity across the Park would support efforts to remove the Park from UNESCO's List of World Heritage In Danger.